The Influence Of Compensation, Leadership, And Work Environment On Employee Job Satisfaction At PT. Bank Rakyat Indonesia KC Unit Padang Jati Bengkulu - Irman Deska Ramadan; Fauzan Fauzan; M. Noor Armi (Utan Kayu Publishing, 2024)
To learn how PT's situation, pay, and work environment affect representatives' levels of job satisfaction. The Padang Jati Bengkulu Unit of Bank BRI KC used surveys to gather data for this survey, and the Purposive Testing method was used to test the results. This study employs an explicative research strategy. Compensation has an effect on job satisfaction (Y) at PT. BRI KC. Unit Padang Jati Bengkulu perceives Ha but pardons Ho with tcountttable and a sig value of 0.000 0.05. Work fulfillment at PT is impacted by drive (Y). BRI KC. Ho's apology is accepted by Unit Padang Jati Bengkulu, and Ha receives a sig with the values 0.005 0.05 and tcountttable. Workplace factors (X3) influence employee satisfaction (Y) at PT. BRI KC. Unit Padang Jati Bengkulu dismisses Ho and acknowledges Ha with tcountttable, with a sig value of 0.004 0.05. Leadership, compensation, and the work environment all have an impact on job satisfaction when Fsig is greater than 0.000 and Fcount is greater than 9.323.